MY SAY: Think of others, please - Abd Razak, Dzulkifli (2008)
Palestinian poet Mahmoud Darwish, who passed away on Aug 9, wrote last year: "One people now have two states, two prisons who don't greet each other. We are victims dressed in executioners' clothing." He should know because he spent many years in exile writing poems dedicated to the struggle of his people. Darwish (meaning a pure, spiritual wandering person in Arabic) later reportedly became heartbroken about the internal strife plaguing his community.